2007
DOI: 10.1016/j.jacc.2007.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of Left Atrial Size in Risk Stratification and Prognosis of Patients Undergoing Stress Echocardiography

Abstract: In patients referred for stress echocardiography, LA size provides independent and incremental value over standard risk factors including left ventricular systolic dysfunction and ischemia. Left atrial size is a powerful prognosticator and should be routinely used in the prognostic interpretation of stress echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 27 publications
4
34
1
3
Order By: Relevance
“…16,19,20) Enlarged LA size in women signifies higher risk compared to men. 21) These findings further emphasize what earlier studies had suggested about the implications of a false positive MPS. Further work up in the form of a transthoracic echocardiogram and aggressive management of CAD risk factors may be appropriate to try to prevent future adverse outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…16,19,20) Enlarged LA size in women signifies higher risk compared to men. 21) These findings further emphasize what earlier studies had suggested about the implications of a false positive MPS. Further work up in the form of a transthoracic echocardiogram and aggressive management of CAD risk factors may be appropriate to try to prevent future adverse outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…8,9 In same utilization, the right heart enlargement carries additional predictive value to that of left ventricular dilation in acquired heart failure 10,11 Enlargement of the left atrium is a risk factor for atrial fibrillation, stroke and death in patients with ischemic heart disease and heart failure. 12,13 As well the outcome of Fallot's tetralogy could be predicted based on left and right ventricular sizes and progressive right ventricular dilation has been employed as a criterion for the timing of pulmonary valve replacement in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…La dilatación auricular, especialmente de la aurícula izquierda, siempre ha sido identificado como un predictor de mayor riesgo de fibrilación auricular, accidente cerebro vascular, y de mortalidad (Bangalore et al 2007, Benjamin et al 1995, Van Wagoner 2008. Aunque la dilatación auricular se presenta en ambas aurículas, hay pruebas sólidas de que en la aurícula izquierda, el alargamiento, determinado por la ecocardiografía, es un predictor robusto de resultados cardiovasculares (Abhayaratna et al 2006).…”
Section: Remodelado Estructural O Dilatación Auricularunclassified
“…En la Figura 3.4 muestra un segmento de cable y los flujos de corrientes. El vector de campo eléctrico (mV/cm), E se define como la caída de potencial mantenida espacialmente en un material: (14) en donde: (15) y es una función escalar para el potencial dentro del cable (o el potencial intracelular, de ahí el subíndice i). Por la ley de Ohm, el vector de flujo J (µA/cm²), el cual representa la densidad de corriente dentro del cable, es proporcional al vector del campo eléctrico (ver la Figura 3.4) (16) Físicamente la ecuación (16), establece que el flujo de corriente en un cable, ocurre en la dirección de la mayor caída de potencial.…”
Section: Teoría Del Cableunclassified
See 1 more Smart Citation